The efficiency in executing the laws and their enforcement regarding pig's waste management: a case study on the Nipah virus outbreak in Negeri Sembilan / Nurul'ain Shafie … [et al.] - Shafie, Nurul'ain; Ramli, Salihah; Ahmad, Suhaidariah; Ismail, Suraya (Faculty of Law, 2009)
Nowadays, pork is the most consumed meat by the people all around the world. Due to this fact, there is an increase demand of pork and intensive pigs rearing have to be done in order to meet the consumers need. The usual problem with the intensive pigs rearing is the improper pig's waste management which eventually will lead to other problems such as environmental pollution and affecting the public's health. This research focuses on the laws and their execution regarding pig's waste management and also to figure out the link between pig's waste management and the outbreak of Nipah virus in Negeri Sembilan in 1999. The final outcome from this research is that the laws and their execution regarding pig's waste management are sufficient and there is no connection between pig's waste management and the outbreak of Nipah virus.